Sosialisasi Membangun Jiwa Kewirausahaan di Kalangan Siswa SMK - Dwinanda, Farhan; Hartinah, Dwi Ayu Siti; Ahmad Ahmad; Harianto, Dedi; Hidayahtullah, Andi Muhammad Syukur (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Community Service Activities aim to build the entrepreneurial spirit of young people in Pengkajoang Village through socialization at the Madani Vocational High School, Malangke. With this service, it is hoped that young people in Pengkajoang Village will be more interested in the world of entrepreneurship because of the abundant natural resources in the village while also overcoming the problem of poverty in the village. The method used in this service is to motivate young people related to fostering the entrepreneurial spirit of young people through socialization at the Madani Vocational High School, Pengkajoang Village, West Malangke. From the results of the service obtained, young people, especially at the Madani Vocational High School in Pengkajoang Village, have a high interest in entrepreneurship, as evidenced by the many questions submitted by students during the service.